Regulation and markets beyond 2000 - Macgregor, Laura; Prosser, Tony; Villiers, Charlotte (Routledge revivals., 2017)
"This title was first published in 2000: The book will be a set of essays addressing various aspects of regulation. It will concentrate on regulation as a precondition of successfully operating markets - by opening up markets and establishing conditions of trust. It will cover a broad range of varied forms of regulation. The book will respond to recent developments, for example, the shift from deregulation to better regulation will be explored. Most chapters will be written jointly by an academic and a legal practitioner (from the commercial solicitors firm of Shepherd and Wedderburn), thus ensuring an integration of theoretical analysis with practical problems."--Provided by publisher